Peningkatan Pengetahuan tentang Pencegahan Infeksi dan Penyebaran Penularan COVID-19 di Panti Asuhan/LKSA Darul Tazkiyah Kota Palangka Raya - Dwi Purbayanti; Rinny Ardina; Halida Suryadini (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
COVID-19 infection regardless of age. It can infect children, adults, and older adults. Children and older adults are high-risk groups of infection. An orphanage where many children live in one place with a high risk of transmission of the SARS-CoV-2 virus. Education about prevention of infection and the spread of COVID-19 transmission at Darul Tazkiyah orphanage Palangka Raya was needed. The implementation methods included a pre-test, education about COVID-19, post-test, and submission of calendars containing information on prevention of COVID-19, posters, betel leaf extract hand sanitizers and health protocols banners. A total of 46 orphanage children became respondents. The paired sample t-test showed that p-value (0.000) <0.05. It meant there was a difference between pre-test and post-test results, which meant there was an increasing children's knowledge about prevention of infection and the spread of COVID-19 transmission at Darul Tazkiyah Orphanage, Palangka Raya. Based on the results of the service activities carried out, it showed that providing education can increase children's knowledge about how efforts to prevent transmission of COVID-19, so it is hoped that this increased knowledge can minimize transmission of COVID-19 and help government programs to reduce positive cases of COVID-19 in Palangka Raya in particular.